2020
DOI: 10.3168/jds.2020-18497
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative detailed milk protein profiles of 6 cattle breeds: Sources of variation and contribution of protein genetic variants

Abstract: Different fractions of milk nitrogenous compounds (not only caseins) have different effects on the nutritional value of milk, its coagulation and curd firming properties, and its cheese-making efficiency. To assess different sources of variation, especially the cows' breed and genetic variants of the main protein fractions, milk samples were collected from 1,504 cows belonging to 3 dairy breeds (Holstein-Friesian, Brown Swiss, and Jersey) and 3 dual-purpose breeds (Simmental, Rendena, and Alpine Grey) reared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 48 publications
5
24
1
1
Order By: Relevance
“…Many previous reports have shown that this unique compositional characteristic of caprine milk is highly correlated with the therapeutic and hypoallergenic properties of its milk in infants and especially in CMPA patients [14,[17][18][19]. Amalfitano et al (2020) [1] reported that in terms of percentage of milk N, the genotypes of CSN3 notably affected all the casein fractions, whereas the BLG genotypes had a much greater influence on most non-casein traits. The genotypes of the CSN2 gene exerted an appreciable effect on α S2 -CN and not β-CN.…”
Section: Beta-casein Genetic Variants and Polymorphismmentioning
confidence: 97%
See 2 more Smart Citations
“…Many previous reports have shown that this unique compositional characteristic of caprine milk is highly correlated with the therapeutic and hypoallergenic properties of its milk in infants and especially in CMPA patients [14,[17][18][19]. Amalfitano et al (2020) [1] reported that in terms of percentage of milk N, the genotypes of CSN3 notably affected all the casein fractions, whereas the BLG genotypes had a much greater influence on most non-casein traits. The genotypes of the CSN2 gene exerted an appreciable effect on α S2 -CN and not β-CN.…”
Section: Beta-casein Genetic Variants and Polymorphismmentioning
confidence: 97%
“…2.0 ± 0.17 a-c Different letters denotes significant difference (p < 0.001). 1 Results are shown as the mean ± SEM (n = 3; n = 2 for A 1 ). 2 t pep = reaction time with pepsin.…”
Section: Formation Of Bcm-7 Its Bioactivity and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed profiling of milk protein and nonprotein nitrogenous compounds was based on 3 groups of information that were reported in our previous study on the effects of breed (Amalfitano et al, 2020). Briefly, the first group was 3 N compounds (protein, CN, and urea) analyzed with the Fourier-transform infrared spectroscopy (FTIR) methods officially used for milk recording (ICAR, 2012).…”
Section: Analysis Of Detailed Milk Protein and Nonprotein Profilesmentioning
confidence: 99%
“…Like all quantitative traits, the protein content during the crossing is inherited intermediately. However, the increase in the range of variability of the trait enables breeders to use individual selection methods to obtain a positive effect in the next generation (Amalfitano et al, 2020). In the experiment conducted by Shkurko (2005), it was determined that all groups had a high percentage of fat and relatively low protein content.…”
Section: Introductionmentioning
confidence: 99%